An Analysis of Rabies Incidence and Its Geographic Spread in the Buffer Area Among Orally Vaccinated Wildlife in Ukraine From 2012 to 2016 - Polupan, Ivan; Bezymennyi, Maksym; Gibaliuk, Yurii; Drozhzhe, Zhanna; Rudoi, Oleksii; Ukhovskyi, Vitalii; Nedosekov, Vitalii; De Nardi, Marco (Frontiers in Veterinary Science, 2019)
The statistics of rabies cases in Volyn, Lviv and Zakarpattia oblasts of Ukraine from 2012-2016 have been analyzed to establish spatial-temporal laws of rabies enzootic outbreaks and identify causes of the widespread infection occurrence among wild and domestic animals. Estimations of the rabies enzootic outbreaks in Ukraine were conducted to identify the influence of oral rabies vaccination (ORV) campaigns in foxes carried out during 2012-2016. Rabies infection is a complicated problem in Ukraine for both veterinary medicine and the public health service. Parenteral vaccination campaigns of domestic animals and foxes have not had a sufficient influence on enzootic rabies outbreaks for a long period of time. ORV campaigns in foxes were determined to be not efficient after studying enzootic rabies outbreaks in western Ukraine (Volyn, Lviv and Zakarpattia oblasts) in 2012-2016. The current rabies prevention system was also determined to be insufficient among domestic animals after reviewing enzootic rabies outbreaks in dogs and cats, i.e. statistically significant clusters (p<0.05). ORV campaign shortcomings and their causes must be determined in order to provide maximum rabies vaccine coverage of dogs and cats. The results presented will be useful to efficiently distribute disease control efforts.